Learn Azure Administration - Mrzyglod, Kamil (Packt Publishing, 2020)
Enhance your Azure administration and Azure DevOps skills and get up and running with networking, security, automation, and effective cost management Key Features Explore a variety of administration patterns used for different cloud architectures Discover best practices for administering various IT systems hosted in Azure Administer, automate, and manage your Azure cloud environment effectively Book Description Microsoft Azure is one of the upcoming cloud platforms that provide cost-effective solutions and services to help businesses overcome complex infrastructure-related challenges. This book will help you scale your cloud administration skills with Microsoft Azure. Learn Azure Administration starts with an introduction to the management of Azure subscriptions, and then takes you through Azure resource management. Next, you'll configure and manage virtual networks and find out how to integrate them with a set of Azure services. You'll then handle the identity and security for users with the help of Azure Active Directory, and manage access from a single place using policies and defined roles. As you advance, you'll get to grips with receipts to manage a virtual machine. The next set of chapters will teach you how to solve advanced problems such as DDoS protection, load balancing, and networking for containers. You'll also learn how to set up file servers, along with managing and storing backups. Later, you'll review monitoring solutions and backup plans for a host of services. The last set of chapters will help you to integrate different services with Azure Event Grid, Azure Automation, and Azure Logic Apps, and teach you how to manage Azure DevOps. By the end of this Azure book, you'll be proficient enough to easily administer your Azure-based cloud environment. What you will learn Explore different Azure services and understand the correlation between them Secure and integrate different Azure components Work with a variety of identity and access management (IAM) models Find out how to set up monitoring and logging solutions Build a complete skill set of Azure administration activities with Azure DevOps Discover efficient scaling patterns for small and large workloads Who this book is for This book is for cloud administrators, system administrators, and IT professionals who want to scale up their skillset and enter the world of cloud computing. IT professionals and engineers who are already familiar with the basics of the Azure services and...